Practice-Driven Research on Enterprise Transformation Second Working Conference, PRET 2010, Delft, The Netherlands, November 11, 2010. Proceedings - Harmsen, Frank; Proper, Erik.; Schalkwijk, Frank; Barjis, Joseph; Overbeek, Sietse; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This volume constitutes the proceedings of the Second Working Conference on Practice-Driven Research on Enterprise Transformation (PRET), held in Delft, The Netherlands, on November 11, 2010. PRET acts as a platform to bridge the gap between theory and practice, and strives for synergy and cross-fertilization between industry and academia. Thus all authors have been asked to combine theory and practice by using real-life case studies and referring to practical experiences. The 9 papers presented were carefully reviewed and selected from 24 submissions, and are grouped in three sections on situational transformation; portfolio, program and project management; and enterprise architecture to align business and IT.
Situational Transformation -- Design and Engineering for Situational Transformation -- Building Blocks for Enterprise Architecture Management Solutions -- Organizational and Design Engineering of the Operational and Support Components of an Organization: The Portuguese Air Force Case Study -- Portfolio, Program and Project Management -- Architecture-Based IT Portfolio Valuation -- Project Portfolio Management in Practice -- Systemic IT Project Management: A Rational Way to Manage Irrationalities in IT Projects? -- Enterprise Architecture to Align Business and IT -- On Supporting Collaborative Problem Solving in Enterprise Architecture Creation -- Dealing with IT Risk in Nine Major Dutch Organizations -- Lines in the Water.
Keywords: Economics; Software engineering; Information systems; Information Systems; Management information systems; Economics/Management Science; Business Information Systems; Computer Appl. in Administrative Data Processing; Information Systems Applications (incl.Internet).; Software Engineering; Management of Computing and Information Systems